Using Discriminant Analysis for Building a Model to Predict Corporate Financial Failure - Mahmmood Alzawbaee, Obaid; Mustafa Ali, Hasan; Obaid Mahmood, Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Companies face the risk of financial failure, which led to the emergence of the need to constantly study the phenomenon of financial failure. Whereas, models of financial failure based on financial ratios circulated in financial analysis have been developed and reached remarkable results in predicting financial failure long before its occurrence, and the study was continued on the models to predict financial failure until the Edward Altman discriminatory model was reached in 1968, which is considered the best model so far. In this research, a model was built to predict financial failure and compared it with Altman’s model in terms of the strength of discrimination. Hence, the model that was built showed that it has a greater discrimination strength than the Altman model when applying them on the same data. In which the percentage of correct classification reached 94.12% of the proposed model, while the percentage of correct classification was 88% for the Altman model, and that the proposed model does not include a gray area in the classification as in the Altman model, but rather classifies all vocabulary into successful and failed.